2013
DOI: 10.1007/s00586-013-3020-1
|View full text |Cite
|
Sign up to set email alerts
|

Chêneau brace for adolescent idiopathic scoliosis: long-term results. Can it prevent surgery?

Abstract: Objective The aim of this study was to evaluate the effectiveness of Chêneau brace in the management of idiopathic scoliosis. Methods This is a retrospective observational study according to SOSORT and SRS (Scoliosis Research Society) recommendations involving 48 girls with documented progressive idiopathic scoliosis, treated with Chêneau brace. A statistical analysis was performed with STATA MP11.2 to validate the obtained results. Results No patient needed surgery. The average curve angle measured in Cobb d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 17 publications
4
54
2
6
Order By: Relevance
“…The Chêneau brace resulted in a higher percentage of correction for thoracic curves at the final follow-up; however, it may not prevent curve progression effectively for double major curves. The results of the present study differed from those of De Giorgi et al, 5 who reported a high percentage of correction for all curves and a more significant percentage of correction at the final follow-up for thoracolumbar curves. However, there may have been a bias in their study because of the small sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…The Chêneau brace resulted in a higher percentage of correction for thoracic curves at the final follow-up; however, it may not prevent curve progression effectively for double major curves. The results of the present study differed from those of De Giorgi et al, 5 who reported a high percentage of correction for all curves and a more significant percentage of correction at the final follow-up for thoracolumbar curves. However, there may have been a bias in their study because of the small sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent retrospective cohort study on Chêneau braces 26 from Italy, the authors report high in-brace corrections and a success rate of more than 95% as published in 2012 in a series of the first author 15 . However, the average Cobb angle in the sample of patients from Italy as reported is n early reduction of the curvature, the earliest onset of treatment with the highest in-brace correction is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Patients should be instructed that the correction of the spine takes place only when the brace is on the body. Morevoer, the effectiveness of the Chêneau brace in halting the progression of the AIS has been experimentally proven 18 . Although full-time bracing has the longest history, some negative psychosocial effects of daytime bracing have led to the study of part-time bracing protocols (using e.g.…”
Section: Discussionmentioning
confidence: 99%